O ensino de arte no contexto da proposta curricular paulista - Silva, Camila Aparecida da (2013)
The purpose of this research is the Curriculum Proposal for the teaching of Art implanted by the State Department of Education of the State of S??o Paulo in the year of 2007/2008. From 2010 the Curriculum Proposal was renamed as Official Curriculum. Our aim is to check if the pedagogical practice of the teaching of Art and the teacher autonomy from this discipline have been affected against the actions of SEE/SP. The study begins with a cutting on the Art/education history in Brazil with the aim to contextualize the transformations of the Art discipline throughout the years for a better comprehension of its nature and needs. To understand the concept and the guidelines that justify the curriculum proposal of Art we analyzed the officials documents produced by the SEE/SP. To verify the possible impacts at a teacher work we carried out a series of interviews with teachers from the public system that teach the Art discipline. This research shows a worrying situation regarding the actual conditions of work at school field by the art/teachers, a contradictory scene that aims a improving at the quality of the education in the State. This panorama revels a professional with weak autonomy by the recent transformations, establishing a new pedagogical practice and points out to a need of a reformulation of educational public policies that includes this professional as a fundamental agent in its processes.